Changes Within H3K4me3-Marked Histone Reveal Molecular Background of Neutrophil Functional Plasticity - Piatek, Paweł; Namiecinska, Magdalena; Lewkowicz, Natalia; Kulińska-Michalska, Małgorzata; Jabłonowski, Zbigniew; Matysiak, Mariola; Dulska, Justyna; Michlewska, Sylwia; Wieczorek, Marek; Lewkowicz, Przemysław (Frontiers in Immunology, 2022)
Neutrophils are a heterogenous population capable of both anti-microbial functions and suppressor ones, however, no specific pattern of transcription factors controlling this plasticity has not been identified. We observed rapid changes in the neutrophil status after stimulation with LPS, pre-activating concentration of TNF-alfa or IL-10. Chromatin immunoprecipitation sequencing (ChIP-Seq) analysis of histone H3K4me3 allowed us to identify various transcriptional start sites (TSSs) associated with plasticity and heterogeneity of human neutrophils. Gene Ontology analysis demonstrated great variation within target genes responsible for neutrophil activation, cytokine production, apoptosis, histone remodelling as well as NF-kappaB transcription factor pathways. These data allowed us to assign specific target genes positioned by H3K4me3-marked histone with different pattern of gene expression related to NF-kappaB pathways, apoptosis and specific profile of cytokines/chemokines/growth factors realised by neutrophils stimulated by LPS, IL-10 or TNF-alfa. We discovered IL-10-induced apoptotic neutrophils being transcriptionally active cells capable of switching the profile of cytokines/chemokines/growth factors desired in resolving inflammation via non-canonical NF-kappaB pathway with simultaneously inhibition of canonical NF-kappaB pathway. As apoptotic/suppressive neutrophils induced by IL-10 via positioning genes within H3K4me3-marked histone were transcriptionally active, newly described DNA binding sites can be considered as potential targets for immunotherapy.